1995
DOI: 10.1103/physrevlett.74.4539
|View full text |Cite
|
Sign up to set email alerts
|

Soliton Contribution to the Electron Paramagnetic Resonance Linewidth in the Two-Dimensional Antiferromagnetic

Abstract: An observed exponential decay in the electron paramagnetic resonance linewidth of the nearly classical two-dimensional antiferromagnet as a function of temperature is shown to be the result of solitons interacting with magnons, and provides an experimental confirmation of these excitations. The temperature dependence of the linewidth is calculated using the dynamic spin correlation function derived from soliton-magnon scattering in the Born approximation. Data in the critical regime for (n-propylammonium) 2 te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
43
1

Year Published

2001
2001
2009
2009

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 17 publications
1
43
1
Order By: Relevance
“…The presence of a small vacancy in the skyrmion center and/or an in-plane magnetic field may induce a rotational mode of the cores around each other, causing important consequences for the spin dynamics. Our results also justify the value % 4pJS 2 obtained theoretically by some authors [15,16] for the Arrhenius EPR linewidth expð4pJS 2 =TÞ temperature dependence of layered magnetic materials and observed experimentally [15,16]. Really, we have shown that, in an infinite lattice, the discreteness effects do not change appreciably the usual skyrmion energy, which is lim L-1 E s ðLÞ-4pJS 2 .…”
Section: Discussionsupporting
confidence: 89%
“…The presence of a small vacancy in the skyrmion center and/or an in-plane magnetic field may induce a rotational mode of the cores around each other, causing important consequences for the spin dynamics. Our results also justify the value % 4pJS 2 obtained theoretically by some authors [15,16] for the Arrhenius EPR linewidth expð4pJS 2 =TÞ temperature dependence of layered magnetic materials and observed experimentally [15,16]. Really, we have shown that, in an infinite lattice, the discreteness effects do not change appreciably the usual skyrmion energy, which is lim L-1 E s ðLÞ-4pJS 2 .…”
Section: Discussionsupporting
confidence: 89%
“…11) was used to explain the EPR line-width in easy-axis (EA) magnets. [12][13][14][15][16][17][18] The classical example of a localized soliton is BP-solution, which exists in isotropic magnets. The scattering problem for such solitons allows an exact analytical solution because of the scale-and conformal-invariance of the model.…”
Section: Introductionmentioning
confidence: 99%
“…In two-dimensional (2D) magnets with nearest-neighbour isotropic Heisenberg interaction-J 1 P S i S k , Skyrmions [1] as localised excitations were extensively treated theoretically [2][3][4][5]. Experimentally, Skyrmions were indirectly observed in layered antiferromagnets, where dipoledipole interaction is small [3,6].…”
Section: Introductionmentioning
confidence: 99%